Transdermal fentanyl induced paralytic intestinal obstruction in advanced liver cancer: a case report - Li, Chen; Chu, Jindong; Jia, Xiaodong; Su, Haibin (Frontiers in Pharmacology, 2025)
IntroductionTransdermal fentanyl (TDF) is a commonly used analgesic drug for managing moderate-to-severe chronic cancer pain. Similar to those observed during the administration of other opioid agonists, the most frequently observed adverse drug reactions during TDF administration include nausea, vomiting, and constipation. However, there have been no reports of TDF causing intestinal obstruction yet. We report a case of TDF-induced paralytic intestinal obstruction confirmed by clinical presentations and imaging findings.Case presentationWe administered TDF (4.2 mg once every 72 h) for external use to a patient who was admitted with acute upper gastrointestinal bleeding, suffering from advanced liver cancer, and having previously received irregular analgesia. Despite achieving satisfactory analgesic effects, he developed nausea, vomiting, constipation, reduced anal exhaust, and absence of bowel sounds on the fifth day of TDF administration. An X-ray test revealed the presence of flatulence and signs of air fluid levels in the intestine. Conventional treatment was ineffective, and paralytic intestinal obstruction was finally alleviated only after TDF was substituted with oral morphine.ConclusionOur findings indicate that, even when TDF is administered in conventional doses, there is a risk of inducing rare cases of intestinal obstruction. In the event of such an occurrence, adjusting the analgesic treatment plan should be the utmost priority.